Physical characteristics and drying kinetics of Portuguese "Longal" chestnut - Ramalhosa, Elsa (2011)
Chestnut is a fruit of great importance in Portugal, being generally sold fresh or frozen. Alternative products may be obtained by hot air drying. The present work is on the dehydration behavior of Portuguese ‘Longal’ chestnut, that is the most used in industry. Different models for representing the variations of water content and drying rate along time were tested successfully. As expected, higher temperatures correspond to faster drying processes. The apparent diffusivity was predicted by Fick’s second law equation, and it ranged from 1.25x10-11 m2/s, at 20ºC, to 8.42x10-10 m2/s, at 100ºC.